The relationship between rumination and job fatigue in pre-hospital emergency personnel: a cross-sectional study - Ehsan kamalifar; Hosein Asadi; Saeid Mehri (BMC Emergency Medicine)
Abstract Background This study examines the relationship between rumination and job Fatigue among pre-hospital emergency personnel in Ardabil Province, as well as the role of demographic and occupational factors in shaping these outcomes. Methods This cross-sectional descriptive study included 338 pre-hospital emergency personnel from Ardabil Province, selected through census sampling. Data were collected using the Nolen-Hoeksema and Morrow Rumination Questionnaire, which measures general rumination, and the Swedish Job Fatigue Inventory to assess Job fatigue. Descriptive statistics, t-tests, and ANOVA were performed using SPSS software. Results The mean total score for job fatigue was 93.14 ± 10.32, while the mean score for rumination was 53.12 ± 10.34, both indicating moderate levels. Significant correlations were found between job fatigue and demographic or occupational factors such as age (p = 0.02), work experience (p < 0.001), workplace (p < 0.001), and shift type (p < 0.001). Regarding rumination, significant associations were also observed with age (p = 0.03), work experience (p < 0.001), and workplace (p < 0.001). Additionally, shift type showed a significant relationship with rumination (p < 0.001). Conclusions Demographic and job-related factors, including age, work experience, workplace, and shift type, significantly affect the levels of rumination and job fatigue in pre-hospital emergency personnel. Implementing targeted support programs and optimizing shift management may help reduce psychological strain in this workforce. Clinical trial number Not applicable.